Previous alpine grazing experience of cows has little medium-term effect on feeding behaviour, milk yield and composition in a traditional alpine system - Madeline Koczura; Steve Pervier; Elisa Manzocchi; Germano Turille; Rupert M. Bruckmaier; Michael Kreuzer; Joel Berard (Italian Journal of Animal Science, 2019)
Previous grazing experience on high alpine pastures may help cows to optimise feed selection and minimise impairments in milk production. Eight inexperienced and eight experienced Aosta Red Pied cows were compared (primiparous:multiparous = 1:1). Measurements were performed when cows grazed sites at 600, 1800 and 2100 m a.s.l. The statistical model included experience, parity and site as fixed effects. The longest ingestion time was recorded for primiparous inexperienced cows at 1800 m a.s.l. Milk yield remained unaffected by experience, but the main milking time was shorter in inexperienced cows in the lowlands. Milk of inexperienced cows had a higher urea content than experienced cows. Somatic cell score remained unaffected by experience, but inexperienced cows had more incidences of clinical mastitis on alpine pastures. Compared with experienced cows, proportions of the fatty acids ΣC16:1 and ΣC17:1 in milk fat of inexperienced cows were higher and proportions of C18:1 t9 and C18:1 t6–8 lower. Overall, alpine grazing had substantial effects on milk yield and composition coinciding with results from previous studies. There were interactions between experience and site in milking characteristics and milk composition, and for the latter also between experience and parity. In conclusion, experience had effects on several of the variables tested, effects which were sometimes exhibited already on lowland pasture. Still, the effects of experience were much lower than those of the transhumance system.Highlights The advantages of previous site-specific and age experience of cows were studied on alpine pasture. Lack of experience had mostly minor effects on economically relevant traits. Experience helped to maintain udder health in this alpine environment.